L’Orient méditerranéen du Moyen âge chrétien : La rencontre de l’Islam - Hentsch, Thierry (Études internationales, 1986)
Anachronism is one of the most common distorsions of history by which we circumscribe the past with our own mental universe. That is what the modem West has done and continues to do as regards Islam - a society almost without distinction of time or space. Thus today the encounter between Western Christendom and Islam is commonly seen as essentially negative, having been reduced to the military - religious conflict of the Crusades during the ll,h and 13,h centuries. Of course, it was at that period of time that took shape a Catholic view of Islam as a religion obnoxiously stereotyped, a view which would spread across Europe and which, much later, would give rise to a truly different form of racism, still around to day. Such an overall despising attitude tends to cover up the positive aspects of what had been the encounter between Islam and Christianity. Y et, those were many and they have been invaluable in the development of the Western thought and sciences. Far from being only a region of conflict, at that time the Mediterranean was also a zone of cultural symbiosis to which the modem West owes much. Europe would do well to remember this today that its supremacy is already part of a past which is definitely over.